THEMATIC GROUPS OF PHILOSOPHICAL TERMINOLOGY IN UZBEK AND ENGLISH LANGUAGES - Islom Boynazarov (American Journals Publishing, 2024)
This comprehensive investigation explores the thematic groups of philosophical terms, analyzing their nuances in both English and Uzbek linguistic contexts. The identified clusters—Metaphysics, Epistemology, Logic, Ethics, and Aesthetics—emerge as foundational pillars in philosophy, each delving into distinct aspects of human understanding. The study emphasizes the crucial role of linguistic perspectives in fostering precision, clarity, and cross-cultural understanding in philosophical communication. This scholarly exploration underscores the globalized nature of philosophical inquiry, advocating for linguistic considerations to promote inclusivity, avoid misinterpretations, and facilitate comparative analyses across diverse philosophical traditions.
Keywords: Thematic groups, philosophical terms, metaphysics, epistemology, logic, ethics, aesthetics, English, Uzbek.